SITTING POSTURE AND COGNITIVE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW (Jurnal Arsitektur ARCADE, 2026)
Poor sitting posture is suspected to affect cognitive functions such as attention and processing speed, yet empirical evidence remains inconsistent. This systematic literature review aimed to identify effective research protocols, summarize findings, and provide measurement guidelines for cognitive performance in sitting posture studies. A systematic search was conducted in Scopus, PubMed, and Google Scholar (2016–2026) using keywords related to sitting posture and cognition. Inclusion criteria were healthy adults, seated activity, and objective attention/concentration measures. From an initial 276 records, ten studies met the inclusion criteria. Results showed that upright or ergonomically supported sitting posture consistently improved processing speed (effect sizes ranging from d= 0.30 to 0.42) and reduced reaction time compared to slumped posture. Selective attention improved with upright posture or active chairs (e.g., CoreChair, seated whole-body vibration), whereas higher‑order executive functions (switching, updating, multitasking) were not significantly affected across the reviewed studies. Most studies found that sitting longer than 90 minutes was associated with increased cognitive errors, with age and daily working hours acting as moderators. In conclusion, upright ergonomic sitting benefits processing speed and selective attention. Effective protocols include 15–30 minutes testing duration, standardized tasks (Stroop, flanker, d2‑R), and baseline posture control. Adjusting seat depth, using active chairs, or providing ergonomic training is recommended to improve cognitive performance in workplace and educational settings.